New records of mosquito species for central and Cuyo regions in Argentina - Visintin, Andrés Mario (2009)
The geographical distributions of Aedes aegypti, Culex apicinus, Cx. educator, Cx. interfor, Cx. quinquefasciatus, Mansonia humeralis, Ma. indubitans, and Psorophora albigenu/varipes are extended, including new records for 2 provinces.